KERALA State Government versus Commercial Banks (Economic and Political Weekly December 5, 1998, 1998)
In no other state have the operations of commercial banks been subjected to such close scrutiny as in Kerala. The state government and the banks have been engaged in a war of words over the banks' low credit-deposit ratio in the state. Where does the truth lie?